2018
DOI: 10.1021/acs.jpclett.8b00700
|View full text |Cite
|
Sign up to set email alerts
|

Self-Powered All-Inorganic Perovskite Microcrystal Photodetectors with High Detectivity

Abstract: Organic-inorganic lead halide perovskite microcrystal (MC) films are attractive candidates for fabricating high-performance large-area self-powered photodetectors (PDs) because of their lower trap state density and higher carrier mobility than their polycrystalline counterparts and more suitability of synthesizing large lateral area films than their single-crystal counterparts. Here, we report on the fabrication of self-powered all-inorganic CsPbBr perovskite MC PDs with high detectivity, using a modified solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
101
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(105 citation statements)
references
References 39 publications
4
101
0
Order By: Relevance
“…Yang et al reported that single crystalline perovskite PDs exhibits superior performance than its polycrystalline counterpart, with recorded photoconductive gain of 50 million . However, due to the long charge carrier diffusion length and poor carrier collection efficiency, many reported inorganic perovskite PDs with large grain‐size crystal show large dark current, limited responsivity, and slow photoresponse …”
Section: Performance Comparison Of Self‐powered Pds Based On Hybrid Pmentioning
confidence: 99%
“…Yang et al reported that single crystalline perovskite PDs exhibits superior performance than its polycrystalline counterpart, with recorded photoconductive gain of 50 million . However, due to the long charge carrier diffusion length and poor carrier collection efficiency, many reported inorganic perovskite PDs with large grain‐size crystal show large dark current, limited responsivity, and slow photoresponse …”
Section: Performance Comparison Of Self‐powered Pds Based On Hybrid Pmentioning
confidence: 99%
“…Recently, solution‐processed organic–inorganic halide perovskite (OIHP) materials have garnered tremendous attention in the optoelectronic device application sphere, due to their advantageous properties, such as long carrier lifetime, relatively large carrier mobility, and low trap‐state density . These merits enabled perovskite visible light photodetectors with both high sensitivity and fast response speed . Yet, solution‐processed visible‐blind perovskite UV photodetectors, despite their advances, are still far from the performance offered by high‐temperature‐processed commercial visible‐blind UV photodetectors (see Table S1, Supporting Information).…”
Section: Introductionmentioning
confidence: 99%
“…10-17 In addition, OIHP meterials are emerging with excellent electrical and optical properties in such as low excitonic binding energy, high charge carrier mobility, long carrier lifetime, and charge diffusion length, which have attracted great interest and contributed all various of high-performance photodetectors. [18][19][20][21][22][23][24][25] For OIHP photodetectors, excellent performance parameters including responsivity…”
mentioning
confidence: 99%